ANALISIS VEGETASI HUTAN TAMAN NASIONAL GUNUNG RINJANI RESORT JOBEN KABUPATEN LOMBOK TIMUR - Subagio Subagio (IKIP Mataram, 2015)
This research was aimed at analyzing the forest vegetation of National Parkin Rinjani Mountain for developing plant ecology practicum guide. This research was pure research with descriptive explorative design. This research was donein Resort Joben, Rinjani Mountain.The sample that were used in this research was taken based on the area by using area sampling technique. The data collection were analyzed by using Mullerand Dombois Ellenberg theories. Based on the analysis of the data collection, it was found that there were 44 plant sin 3 level sin individual class ifying which 34 type sofs take with KlokosUdang were dominated, 37 type sofmast with Lembokek were dominated and 23 type softree with Dadap were dominated. Based on the observation and analysis of the data in Resort Joben, Rinjani Mountain, it was found that 34 type sofs take with 238 units; 37 type sofmast with 166 units; and 23 type soft tree with 357 units, there fore the total number of regeneration level was 44 types with 761 units. The highest level of Important Value (IV) index was type sof mast which was 294.1. There sult of validity from practicum guides was shown that the mean score was 3.07 with good category. According to the finding sand discussion of this research, it can be concluded that there is some vegetation type sof National Parkin Resort Joben, Rinjani Mountain, and according to the result of practicum guide validity, it was shown that the result of this research was feasible and in good category